Activist hedge fund success: The role of reputation - Wiersema, Margarethe; Ahn, Albert; Zhang, Yu (Strategic Management Journal, 2020)
Abstract Research Summary Activist hedge funds are the new breed of corporate raiders, yet we know little about how the management and board of target firms respond to activist investors. Using a behavioral perspective, we propose that an activist's reputation for being confrontational conveys information to the target company as to what they are likely to encounter in an activist campaign. To avoid the potential adverse consequences of engaging in such a contest, we propose and find that target companies are more likely to settle with an activist known for being confrontational. Our study contributes to corporate governance research by providing insight into the importance of the social context surrounding activist campaigns and the role of reputation in influencing how companies respond to activist investors. Managerial Summary Given that hedge fund activism is having a major impact on firm's strategic and financial decision‐making, it is important to understand how these activist investors influence companies. An activist campaign is a highly disruptive event leading to considerable ambiguity and uncertainty as to what is likely to transpire. Given this information void, our study finds that the board and management respond based on the reputation of the activist investor that has taken a stake in the company. That activist investors with a reputation for being hostile are more successful may be a defensive response on the part of management in order to avoid the potential adverse consequences of a hostile campaign. This has implications for corporate governance and the fiduciary duty of the board.